2022
DOI: 10.1016/j.ribaf.2021.101602
|View full text |Cite
|
Sign up to set email alerts
|

The market reaction to syndicated loan announcements before and during the COVID-19 pandemic and the role of corporate governance

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 110 publications
1
2
0
Order By: Relevance
“…It was concluded that good corporate governance could help to mitigate the negative effects of COVID-19 on stock price volatility and trading volume, but it may help alleviate the impact of COVID-19 on stock returns. Nevertheless, the results of this study reinforce the conclusion of [115], that a firm's ability to adapt to changes in the external environment (COVID-19) might be hindered by a rigid and strict CG framework. The argument of this study, however,-through a strategic viewpoint-goes beyond the "traditionally" considered CG factors, such as board size, gender diversity, a link between CEO compensation and shareholder return, or CEO duality.…”
Section: Comparison Of the Results Of Esg And Covid-19 Researchsupporting
confidence: 83%
“…It was concluded that good corporate governance could help to mitigate the negative effects of COVID-19 on stock price volatility and trading volume, but it may help alleviate the impact of COVID-19 on stock returns. Nevertheless, the results of this study reinforce the conclusion of [115], that a firm's ability to adapt to changes in the external environment (COVID-19) might be hindered by a rigid and strict CG framework. The argument of this study, however,-through a strategic viewpoint-goes beyond the "traditionally" considered CG factors, such as board size, gender diversity, a link between CEO compensation and shareholder return, or CEO duality.…”
Section: Comparison Of the Results Of Esg And Covid-19 Researchsupporting
confidence: 83%
“…The literature on market reactions in various conditions is reportedly increasing among various scholars. Based on these literature reviews, market reactions are associated with war [21][22][23][24][25], loan announcements, corporate governance [26], and audit reports [27]. In the coal industry, environmental policy also affected market reactions negatively [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, GCG principles could help a corporation elevate its ability to respond to oscillations in the external surroundings of the business by taking appropriate measures (Le and Nguyen 2022). According to Tampakoudis et al (2022), CG mechanisms pertain differently to borrowers' overplus before and after the COVID-19 pandemic (Tampakoudis et al 2022). Nurdiani and Anas (2022) indicated that GCG and risk management had significant effects on business performance during the COVID 19 pandemic (Nurdiani and Anas 2022).…”
Section: Corporate Governancementioning
confidence: 99%